2008
DOI: 10.3402/fnr.v52i0.1654
|View full text |Cite
|
Sign up to set email alerts
|

Calcium intake in elderly patients with hip fractures

Abstract: Background: Dietary calcium intake is assumed important in the prevention and treatment of osteoporosis. However, people in countries with a high calcium intake from commodities such as milk and milk products have a high incidence of hip fracture. The effect and influence of calcium intake in the prevention of osteoporotic fracture vary from different studies. Objective: To investigate premorbid daily calcium intake in patients with low energy hip fractures during four consecutive years. Design: In total 120 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…Majority of the patients in our study showed a predominance of femur fractures as compared to other fractures. These findings were similar to the previous studies carried out on calcium intake in elderly patients with osteoporotic fractures which showed higher incidence of femur fractures [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…Majority of the patients in our study showed a predominance of femur fractures as compared to other fractures. These findings were similar to the previous studies carried out on calcium intake in elderly patients with osteoporotic fractures which showed higher incidence of femur fractures [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…Evaluation of calcium intake in a group of elderly patients with hip fractures showed that their mean calcium intake was above the recommended daily intake of 800 mg/d (Cho et al, 2008). However, more than onethird of these patients had a lower intake.…”
Section: Calcium Intake and Fracture Riskmentioning
confidence: 96%
“…qual o leite, o iogurte e o queijo compunham 686mg (71%); e uma suplementação média de Ca referente à 284mg (29%); ao longo de quatro anos, pesquisadores observaram uma tendência à ingestão de Ca diminuída gradualmente, através dos alimentos, em 27% dos pacientes; e de suplementos em 63% dos pacientes. Nesses casos, a média de ingestão de Ca se apresentou bem acima da ingestão diária recomendada, independentemente do sexo 25 . No entanto, vale ressaltar que, mais de um terço dos indivíduos apresentavam consumo abaixo do nível recomendado.…”
Section: Suplementação Nutricional Osteoporose E Fraturasunclassified